Teachers' Participation in Academic Affairs Administration in Rayong 1 School Consortium under the Secondary Educational Service Area Office Chonburi Rayong - กีรติกิตติกัลยา, ดิศกุล; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research on Teachers' Participation in Academic Affairs Administration in Rayong 1 School Consortium under the Secondary Educational Service Area Office Chonburi Rayong had the following objectives: 1) to study teachers' participation in academic administration, 2) to compare teachers' participation in academic administration, and 3) to identify guidelines for developing. The sample consisted of 309 government teachers' participation in academic affairs administration determined using Taro Yamane table. Stratified random sampling was employed with simple random sampling through lottery drawing. The research instrument was a 5-level rating scale questionnaire. The instrument exhibited an Index of Item-Objective Congruence (IOC) ranging from 0.60 to 1.00, with a reliability coefficient of .977. The research instruments consisted of questionnaires and interviews. Data were analyzed using percentage, mean, standard deviation, t-test, F-test, and content analysis.           The results revealed that: 1) The overall teachers' participation in academic affairs administration in Rayong 1 School Consortium was at a high level. When considered in each aspect, the aspect with the highest mean was Development and Implementation of Educational Technology Media, followed by Research for Educational Quality Development The aspect with the lowest mean was Educational Supervision 2) The comparison of teachers’ participation in academic administration classified by gender, position, educational background, school size, and work experience revealed no significant differences. 3) The guidelines for enhancing teachers’ participation in academic affairs administration in schools consist of seven aspects: Driving excellence through a results-driven vision, aligned active learning, and quality-based benchmarking, powered by PLC collaboration, a positive learning climate, PDCA management, and technological integration.